Delivery of mesenchymal stem cells in biomimetic engineered scaffolds promotes healing of diabetic ulcers. (April 2016) - Assi, Roland; Foster, Trenton R; He, Hao; Stamati, Katerina; Bai, Hualong; Huang, Yuegao; Hyder, Fahmeed; Rothman, Douglas; Shu, Chang; Homer-Vanniasinkam, Shervanthi; Cheema, Umber; Dardik, Alan
Aim: We hypothesized that delivery of mesenchymal stem cells (MSCs) in a biomimetic collagen scaffold improves wound healing in a diabetic mouse model.Materials & methods: Rolled collagen scaffolds containing MSCs were implanted or applied topically to diabetic C57BL/6 mice with excisional wounds.Results: Rolled scaffolds were hypoxic, inducing MSC synthesis and secretion of VEGF. Diabetic mice with wounds treated with rolled scaffolds containing MSCs showed increased healing compared with controls. Histologic examination showed increased cellular proliferation, increased VEGF expression and capillary density, and increased numbers of macrophages, fibroblasts and smooth muscle cells. Addition of laminin to the collagen scaffold enhanced these effects.Conclusion: Activated MSCs delivered in a biomimetic-collagen scaffold enhanced wound healing in a translationally relevant diabetic mouse model.